Novel phenotype associated with a mutation in the KCNA1(Kv1.1) gene - D'Adamo, Maria C.; Gallenmüller, Constanze; Servettini, Ilenio; Hartl, Elisabeth; Tucker, Stephen J.; Arning, Larissa; Biskup, Saskia; Grottesi, Alessandro; Guglielmi, Luca; Imbrici, Paola; Bernasconi, Pia; Di Giovanni, Giuseppe; et al. (Frontiers in Physiology, 2015)
Episodic ataxia type 1 (EA1) is an autosomal dominant K+ channelopathy which manifests with short attacks of cerebellar ataxia and dysarthria, and may also show interictal myokymia. Episodes can be triggered by emotional or physical stress, startle response, sudden postural change or fever. Here we describe a 31-year-old man displaying markedly atypical symptoms, including long-lasting attacks of jerking muscle contractions associated with hyperthermia, severe migraine, and a relatively short-sleep phenotype. A single nucleotide change in KCNA1 (c.555C>G) was identified that changes a highly conserved residue (p.C185W) in the first transmembrane segment of the voltage-gated K+ channel Kv1.1. The patient is heterozygous and the mutation was inherited from his asymptomatic mother. Next generation sequencing revealed no variations in the CACNA1A, CACNB4, KCNC3, KCNJ10, PRRT2 or SCN8A genes of either the patient or mother, except for a benign variant in SLC1A3. Functional analysis of the p.C185W mutation in KCNA1 demonstrated a deleterious dominant-negative phenotype where the remaining current displayed slower activation kinetics, subtle changes in voltage-dependence and faster recovery from slow inactivation. Structural modeling also predicts the C185W mutation to be functionally deleterious. This description of novel clinical features, associated with a Kv1.1 mutation highlights a possibly unrecognized relationship between K+ channel dysfunction, hyperthermia and migraine in EA1, and suggests that thorough assessments for these symptoms should be carefully considered for all patients affected by EA1.